Magic broom - Pellowski, Michael; Garry-McCord, Kathleen (Mahwah, N.J. : Troll Associates, 1986)
Brenda Bunny adopts a magic broom on the condition it hide its magic from her parents, but when a robber enters their home the broom reveals its secret.
1.5
K-3
Keywords: Brooms and brushes -- Fiction; Magic -- Fiction; Rabbits -- Fiction; Magic -- Fiction; Rabbits -- Fiction